2011
DOI: 10.1095/biolreprod.110.086983
|View full text |Cite
|
Sign up to set email alerts
|

SIRT1 Is a Novel Regulator of Key Pathways of Human Labor1

Abstract: Human sirtuin (SIRT) 1 and SIRT2, which possess nicotinamide adenosine dinucleotide (NAD(+))-dependent deacetylase activity, exhibit anti-inflammatory actions. However, there are no data available on SIRT1 and SIRT2 expression and regulation in human intrauterine tissues. Thus, the aim of this study was to characterize the localization and expression of SIRT1 and SIRT2 in 1) placenta and fetal membranes before and after term spontaneous labor onset, 2) prelabor fetal membranes from the supracervical site (SCS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
117
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(123 citation statements)
references
References 62 publications
4
117
1
1
Order By: Relevance
“…TIMP-1 was barely detectable; TIMP-2 and TIMP-4 protein were detectable in all specimens but did not change with Strength. Other groups have also confirmed the increase in markers of collagen remodeling and apoptosis (Malak & Bell et al, 1994;El-Khwad et al, 2005Meinert et al, 2007, Reti et al, 2007Han et al, 2008;Lappas et al, 2008Lappas et al, , 2009Lappas et al, , 2010aLappas et al, , 2010b. Using FM from patients with AROM (artificial rupture of membranes) and SROM (spontaneous rupture of membranes), we have further demonstrated that the para-cervical weak zone persists with the same biochemical signature as that identified in pre-labor cesarean section membranes.…”
Section: Term Fm Develops a Para-cervical "Weak Zone" Where Rupture Isupporting
confidence: 67%
“…TIMP-1 was barely detectable; TIMP-2 and TIMP-4 protein were detectable in all specimens but did not change with Strength. Other groups have also confirmed the increase in markers of collagen remodeling and apoptosis (Malak & Bell et al, 1994;El-Khwad et al, 2005Meinert et al, 2007, Reti et al, 2007Han et al, 2008;Lappas et al, 2008Lappas et al, , 2009Lappas et al, , 2010aLappas et al, , 2010b. Using FM from patients with AROM (artificial rupture of membranes) and SROM (spontaneous rupture of membranes), we have further demonstrated that the para-cervical weak zone persists with the same biochemical signature as that identified in pre-labor cesarean section membranes.…”
Section: Term Fm Develops a Para-cervical "Weak Zone" Where Rupture Isupporting
confidence: 67%
“…SIRT1 plays a pivotal role in regulation of NF-κB-dependent proinfl ammatory mediator expression. Many studies in different tissues have shown that effects of resveratrol are via modulation of NF-κB (17). Although these effects have been confi rmed in in vitro studies (5,7), there are no in vivo studies investigating the role of SIRT1 gene expression in renal I/R injury.…”
Section: Discussionmentioning
confidence: 99%
“…Foetal membranes from the non-labouring group were obtained from the supracervical site (SCS). Identification of the SCS was performed as previously detailed (Lappas et al 2011). Briefly, Bonneys blue dye was introduced through the cervix before Caesarean section.…”
Section: Tissue Collectionmentioning
confidence: 99%
“…Upon delivery of the placenta, a blue mark was obvious on the chorion-facing membrane where the dye had been applied. In the after-labour group, foetal membranes from the site of membrane rupture (SOR) as previously described (Lappas et al 2011). Amnion and underlying choriodecidua were collected from along the line of foetal membrane rupture.…”
Section: Tissue Collectionmentioning
confidence: 99%